The strengths and failures of incentive mechanisms in notional defined contribution pension systems - Angelo Marano; Carlo Mazzaferro; Marcello Morciano (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2011)
Public pension systems based on the Notional Defined Contribution (NDC) principle were introduced during the '90s in Italy, Sweden and Poland, among other countries. They mimic private savings, in that individuals get back, as pensioners, what they contributed to social security during working life, plus returns. As such, NDC systems should realize actuarial equity and incentive neutrality. However, when one considers the presence of NDC pensions together with minimum and social assistance pensions, this is no longer true. Indeed, in all the three countries considered, the NDC system shows a regressive feature, which disincentives contributions, particularly from low earners, who would be better off entering, or staying in, the shadow economy. In order to reduce the extent of this phenomenon, we examine the effects of introducing, or increasing, the possibility of accumulation of social assistance and NDC pensions, which would also improve pension adequacy. A complete accumulation of the two would solve the incentive problem, but would be costly and would require a structural reform of the pension system financing mechanism, altering the current balance between social contributions and general fiscal revenues. We show the effects of a change in the accumulation rules for social assistance and NDC pensions in Italy using CAPP DYN, a population-based dynamic micro simulation model, which allows assessment of the evolution of the pension system in the coming decades and the distributional implications of such reform.
Keywords: H55; J26; C51; 330